2020
DOI: 10.3389/fgene.2020.00990
|View full text |Cite
|
Sign up to set email alerts
|

Three Genes Predict Prognosis in Microenvironment of Ovarian Cancer

Abstract: Ovarian cancer (OC) is the deadliest gynecological cancer in women. Immune cell infiltration has a critical role in regulating carcinogenesis and prognosis in OC. To identify prognostic genes relevant to the tumor microenvironment in OC, we investigated the association between OC and gene expression profiles. Results obtained with the ESTIMATE R tool showed that immune score and stromal score were correlated with lymphatic invasion, and high immune score predicted a favorable prognosis. A total of 342 common d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In our study, the AUCs of the signatures at 3, and 5 years were 0.709, 0.762, respectively, which were significantly higher than those of most hallmark predictive models. Table 4 shows that the AUCs of the other three prognostic signatures, namely, the 21 immune‐related gene signature, 35 17 immune‐related gene signature (0.754 at 3 years, 0.824 at 5 years) 36 and 17 transcription factor ‐related gene signature (0.803 at 5 years), 37 were comparable to the predictive capabilities of our predictive model and distinctly higher than those of other signatures, such as the epithelial‐mesenchymal transition related gene signature, 38 TME‐related gene signature, 39,40 RNA‐binding protein‐related gene signature, 41 energy metabolism‐related gene signature, 42 autophagy‐related gene signature, 43,44 ferroptosis‐related gene signature, 45 protein‐coding gene signature, 46 and DNA methylated gene signatures 47 . The larger the AUC value of a biomarker, the better was the predictive ability of the signature, indicating that our gene signature outperformed most of the other signatures in predicting OV prognosis.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…In our study, the AUCs of the signatures at 3, and 5 years were 0.709, 0.762, respectively, which were significantly higher than those of most hallmark predictive models. Table 4 shows that the AUCs of the other three prognostic signatures, namely, the 21 immune‐related gene signature, 35 17 immune‐related gene signature (0.754 at 3 years, 0.824 at 5 years) 36 and 17 transcription factor ‐related gene signature (0.803 at 5 years), 37 were comparable to the predictive capabilities of our predictive model and distinctly higher than those of other signatures, such as the epithelial‐mesenchymal transition related gene signature, 38 TME‐related gene signature, 39,40 RNA‐binding protein‐related gene signature, 41 energy metabolism‐related gene signature, 42 autophagy‐related gene signature, 43,44 ferroptosis‐related gene signature, 45 protein‐coding gene signature, 46 and DNA methylated gene signatures 47 . The larger the AUC value of a biomarker, the better was the predictive ability of the signature, indicating that our gene signature outperformed most of the other signatures in predicting OV prognosis.…”
Section: Resultsmentioning
confidence: 67%
“…The included studies 11,35–47,54–61 used models built based on the TCGA cohort and involved all types of breast cancer. The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV 11,35,38–47,54–61 . Additionally, Yu et al has constructed a five GRG signature (ANGPTL4, PYGB, ISG20, SEH1L and IRS2) for patients with OV 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP12 plays a pivotal role in inflammatory diseases, such as colitis ( Nighot et al, 2021 ) and chronic obstructive pulmonary disease ( Baggio et al, 2020 ). In addition, MMP12 has been regarded as a potential prognostic biomarker for ovarian cancer ( Guo et al, 2020 ) and gallbladder cancer ( Zhao et al, 2019 ). Our results initially identified MMP12 as a negative prognostic biomarker for UM.…”
Section: Discussionmentioning
confidence: 99%
“…But it's controversial whether the expression of PGR serves as the prognostic marker in endometrial cancer. GYPC (glycophorins), is de ned as a negative prognostic biomarker in ovarian cancer [31]. But there has no report about the prognostic value of GYPC in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%